Теоретичні аспекти дослідження схильності людей до комп'ютерних ігор - Ліпець, Зоряна; Сазонова, Олена (Видавництво Львівської політехніки, 2013)
Topicality of the research is caused by the changes which have recently occurred in the field of computer technologies. There has been especially investigated pathological Internet use, so-called Internet addiction, which includes addiction to social networks, dating sites, online auctions, gaming etc. Our attention has been mainly focused on the problem of addiction to playing aggressive computer games. Scientists have not come to the unanimous decision about their harm or benefits yet. On the one hand games improve the intellect, logical thinking, attention and imagination, but on the other hand they slow down the development and can cause musculoskeletal disorders. In terms of psychological study this problem has hardly been investigated in Ukraine. Thus the objective of the research is to discover the connection between the addiction to playing aggressive computer games and factors connected with this addiction, namely aggressiveness, a feeling of loneliness and social frustration. The results of such investigations will help to understand better the reasons for the addiction and possible ways of avoiding it.
Keywords: дослідження; адикція; комп’ютерні ігри; молодь; геймер; гемблінг; класифікація